The theory and practice of undergraduate nursing ethics education programs in South Africa and Namibia : a critical appraisal - De Villiers, Josephine Elizabeth (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.